Beyond the BRICS: power, pluralism, and the future of global order - Hurrell, A (Cambridge University Press, 2018)
People like simple stories and clear narratives. In the early years of the twenty-first century, the narrative of “emerging powers” and “rising powers” seemed to provide a clear and powerful picture of how international relations and global politics were changing. Indeed, there was an upsurge of policy and academic debate about the growing importance of non-Western regions and their leading states—notably Brazil, Russia, India, China, and South Africa, the so-called BRICS—for international politics and the world economy. The story suggested that power was diffusing away from the United States and the West; that the emerging powers were becoming far more consequential actors, both globally and within “their” regions; and that, to remain effective and legitimate, global governance institutions needed to be reformed in order to accommodate their rise.